2017
DOI: 10.1097/mlr.0000000000000819
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Socioeconomic Status Predicts Health After Hospitalization for Acute Coronary Syndromes

Abstract: Objective To explore the influence of contextual factors on health-related quality of life (HRQoL), which is sometimes used as an indicator of quality of care, we examined the association of neighborhood socioeconomic status (NSES) and trajectories of HRQoL after hospitalization for acute coronary syndromes (ACS). Methods We studied 1,481patients hospitalized with ACS in Massachusetts and Georgia querying HRQoL via the mental and physical components of the SF-36 (MCS and PCS) and the physical limitations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Research shows that ischemic heart patients with low socioeconomic status experience worse physical functioning, poorer mental health and health-related quality, and more comorbidity than patients with high socioeconomic status (Barbareschi et al, 2009;Matetic et al, 2020;Nobel et al, 2017). This inequality in the health and well-being of patients living with ischemic heart disease constitute a growing public health problem, which may be related to the rising prevalence of people living with ischemic heart disease since the 1970s (Havranek et al, 2015).…”
Section: Social Inequality In the Experience Of Life With Ischemic He...mentioning
confidence: 99%
See 3 more Smart Citations
“…Research shows that ischemic heart patients with low socioeconomic status experience worse physical functioning, poorer mental health and health-related quality, and more comorbidity than patients with high socioeconomic status (Barbareschi et al, 2009;Matetic et al, 2020;Nobel et al, 2017). This inequality in the health and well-being of patients living with ischemic heart disease constitute a growing public health problem, which may be related to the rising prevalence of people living with ischemic heart disease since the 1970s (Havranek et al, 2015).…”
Section: Social Inequality In the Experience Of Life With Ischemic He...mentioning
confidence: 99%
“…Studies of social inequalities in life with ischemic heart disease tend to use quantitative study design and be based on patient-reported outcomes (PROMs) collected by use of standardized measurement tools (Badarienė et al, 2020;Nobel et al, 2017;Schultz et al, 2018;Shahu et al, 2020). Several generic assessment tools exist enabling exploration of the patient's perceived quality of life, symptoms and functional status, feelings and attitude about illness as well as their experience of healthcare (Forestier et al, 2019).…”
Section: Social Inequality In the Experience Of Life With Ischemic He...mentioning
confidence: 99%
See 2 more Smart Citations